The Influence of Using Jimmy Fallon Talk Show on Students’ English Speaking Achievement - Yustina Gressica Noel; Endang Mastuti Rahayu (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
This study employed a quantitative approach with a true experimental method using a pretest-posttest control group design to examine the influence of using Jimmy Fallon Talk Show on students' speaking achievement. The sample consisted of two classes, each with 32 students, selected through cluster random sampling. Data were collected through speaking tests administered before and after the treatment and analyzed using normality tests and independent t-tests. The results showed a significant improvement in the experimental class compared to the control class, with a higher average posttest score in the group that used the talk show as a learning medium. These findings have implications for teachers, students, and future researchers and provide new insights into the influence of using Jimmy Fallon Talk Show as a medium to enhance students' speaking achievement.